Mechanical performances of twill kenaf woven fiber reinforced polyester composites - Khalid, Siti Nor Azila; Ismail, Al Emran; Zainulabidin, Muhd Hafeez; Tajul Arifin, Ahmad Mubarak; Hassan, Mohd Fahrul; Ibrahim, Rasidi; Rahim, Mohammad Zulafif (UTHM, 2018)
Natural fibres have the potential aspect to replace glass fibre reinforced composites. One of these fibers is kenaf. It is also one of the selected natural fibres that have bio resource profit regarding on their capability to absorb energy absorption especially. In order to prove the application of this fiber for the load-bearing application, the fiber in the form of yarn is weaved into fiber mat and reinforced with the plastic resin. This study focused on the twill yarn kenaf woven composite structure. Composites were prepared using the hand lay-up method with different type of orientation where the orientation is designed using Taguchi method. The hardened composites were cured for 24 hours in an ambient temperature before it was shaped according to ASTM D3039. The samples were then stressed uni-axially to obtain the stress-strain curves. The result shows the fiber orientations were significant factor in determining the performance of tensile strength. In this work, fiber mats are then optimized and the results showed that the values of tensile and modulus strength were 55.738 MPa and 5761.704 Joule, which is increased 3.77% and 4.23% for tensile strength and Young modulus, respectively. By comparing fracture mechanism before and after optimizations, there was clear decreasing fracture surface. It indicated that, the mechanical behavior performances of the twill woven kenaf reinforced composites can be effectively improved by this method.